Echocardiographic measurement of the normal adult right ventricle. Issue 1 (July 1986) - Foale, R; Nihoyannopoulos, P; McKenna, W; Kleinebenne, A; Nadazdin, A; Rowland, E; Smith, G; Klienebenne, A
Abstract : In studies of the right ventricle the complexities of chamber shape may be overcome by use of multiple tomographic imaging planes. An established protocol for the echocardiographic description of the heart was used to examine the right ventricle in an ordered series of transducer locations and orientations. Diastolic measurements were made of the right ventricular inflow tract, outflow tract, and right ventricular body, and the range and reproducibility of normal values for cavity size and right ventricular free wall thickness were established. These measurements of cavity size in 41 normal subjects were highly reproducible and the views that were used correctly described the truncated and ellipsoidal shape of the right ventricular inflow tract and body with a separately aligned outflow tract. Cavity trabeculation prevented measurement of the free wall thickness in some areas; however, values of nearly twice the previously reported upper limit of normal for anterior regions were measured from the apex or lateral right ventricular wall. These normal data provide a basis for future echocardiographic studies of the right ventricle.